The implementation of organizational culture and ethical leadership in building organizational commitments on Islamic Boarding School of Nurul Hakim, Kediri Lombok Barat / Lalu Suparman ... [et al.] - Suparman, Lalu; Nasir, Mahyudin; Suryatni, Mukmin (2019)
Ethical culture and leadership are based on meaningful values, beliefs, and norms of all the organization members. The implementation of organizational culture and ethical leadership is critical for every organization in order to increase their organizational commitment. Despite a number of studies on organizational culture and ethical leadership, lack studies were made on Islamic Boarding School.